Splanchnonema-like species in Pleosporales: introducing Pseudosplanchnonema gen. nov. in Massarinaceae - Chethana, Thilini; Liu, Mei; Ariyawansa, Hiran A.; Konta, Sirinapa; Wanasinghe, Dhanushka N.; Zhou, Ying; Yan, Jiye; Camporesi, Erio; Bulgakov, Timur S.; Chukeatirote, Ekachai; Hyde, Kevin D.; Bahkali, Ali H.; et al. (Phytotaxa, 2015)
In this paper we introduce a new genus Pseudosplanchnonema with P. phorcioides comb. nov., isolated from dead branches of Acer campestre and Morus species. The new genus is confirmed based on morphology and phylogenetic analyses of sequence data. Phylogenetic analyses based on combined LSU and SSU sequence data showed that P. phorcioides formed a distinct clade within the family Massarinaceae and is sister to Massarina eburnea, the type species of Massarina. The new genus Pseudosplanchnonema differs from Massarina in having ascomata without clypei, a thick peridium and larger, 1-septate, guttulate, dark brown ascospores. The new genus is compared with genera in the family Massarinaceae and a detailed description and illustrations of the species P. phorcioides, including its asexual morph, is provided.